2004
DOI: 10.4049/jimmunol.173.6.3660
|View full text |Cite
|
Sign up to set email alerts
|

Fas-Fas Ligand Interactions Are Essential for the Binding to and Killing of Activated Macrophages by γδ T Cells

Abstract: γδ T cells have a direct role in resolving the host immune response to infection by eliminating populations of activated macrophages. Macrophage reactivity resides within the Vγ1/Vδ6.3 subset of γδ T cells, which have the ability to kill activated macrophages following infection with Listeria monocytogenes (Lm). However, it is not known how γδ T cell macrophage cytocidal activity is regulated, or what effector mechanisms γδ T cells use to kill activated macrophages. Using a macrophage-T cell coculture system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 40 publications
2
51
0
Order By: Relevance
“…Previously it was shown that V␥1/V␦6.3 ϩ T cells kill activated macrophages during the late stage of Lm infection (33,42), an activity that is dependent on specific activation of the macrophages, but not of the V␥1/V␦6.3 ϩ T cells, and is TCR mediated (33) and Fas-Fas ligand dependent (52). This study extends these findings by demonstrating that macrophage cytocidal activity is unique to V␥1 ϩ T cells and that these T cells are essential for eliminating activated macrophages and regulating activated macrophage numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Previously it was shown that V␥1/V␦6.3 ϩ T cells kill activated macrophages during the late stage of Lm infection (33,42), an activity that is dependent on specific activation of the macrophages, but not of the V␥1/V␦6.3 ϩ T cells, and is TCR mediated (33) and Fas-Fas ligand dependent (52). This study extends these findings by demonstrating that macrophage cytocidal activity is unique to V␥1 ϩ T cells and that these T cells are essential for eliminating activated macrophages and regulating activated macrophage numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Activation may result in release of proinflammatory chemokines such as XCL1, CXCL1, CCL3, CCL4, and CCL5 45 that are capable of attracting other leukocytes and releasing growth factors such as FGF-7 and FGF-10 41 that influence the division and migration of keratinocytes. In addition, some ␥␦ T-cell subsets limit inflammation or assist in the resolution of inflammation by direct cytotoxic interactions on activated macrophages 46,47 through a mechanism that involves FasL expression on ␥␦ T cells (eg, those expressing V␥1 TCR) interacting with Fas expressed on target cells. 46 There is evidence for anti-inflammatory activity through the production and release of thymosin-␤4, 40 of possible interest in the cornea given published data for an anti-inflammatory and beneficial wound-healing effect of thymosin-␤4 in the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some ␥␦ T-cell subsets limit inflammation or assist in the resolution of inflammation by direct cytotoxic interactions on activated macrophages 46,47 through a mechanism that involves FasL expression on ␥␦ T cells (eg, those expressing V␥1 TCR) interacting with Fas expressed on target cells. 46 There is evidence for anti-inflammatory activity through the production and release of thymosin-␤4, 40 of possible interest in the cornea given published data for an anti-inflammatory and beneficial wound-healing effect of thymosin-␤4 in the cornea. 48,49 The finding that ICAM-1 Ϫ/Ϫ mice exhibited reduced accumulation of ␥␦ T cells and delayed, abbreviated epithelial basal cell division remains to be explained, especially because the CD11a Ϫ/Ϫ mice were not significantly different from wild type.…”
Section: Discussionmentioning
confidence: 99%
“…The death receptor-dependent pathway acts through interactions between Fas with its ligand FasL. One study investigating the mechanism behind Vc1T-cell cytotoxicity showed that FasL expression and Fas-FasL interactions were necessary for cdT-cell killing of infection-elicited activated macrophages 33 The expression of FasL on effector cells is an inducible process. After antigen recognition, the cytotoxic cells synthesized FasL mRNA de novo, translated it into protein and transported it to the cell surfaces through the Golgi.…”
Section: Discussionmentioning
confidence: 99%